Pengaruh Fitness Experience dan Store Atmosphere terhadap Revisit Intention Pelanggan Fitness dengan Customer Satisfaction sebagai Variabel Intervening - Khairiyadi, Mochamad Rizky; Sadat, Andi Muhammad; Rahmi, Rahmi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This study involved 230 respondents to investigate how Fitness Experience and Store Atmosphere influence the Revisit Intention of gym customers through Customer Satisfaction. The questionnaire was distributed online via Google Form. SEM-PLS was used to test the validity, reliability, and hypothesis analysis. Based on the analysis, the results showed adequate validity and reliability. The hypothesis analysis among variables indicated that Fitness Experience, Store Atmosphere, and Customer Satisfaction positively influence the Revisit Intention of gym customers in the Greater Jakarta area (Jabodetabek). Furthermore, Fitness Experience and Store Atmosphere positively influence Customer Satisfaction. Lastly, Store Atmosphere positively influences Fitness Experience.